Effects of Matrix Contact during Gel Filtration of Human Platelets in Plasma - Lindon, Jack N.; Rodvien, Robert; Waugh, David F. (Thrombosis and Haemostasis, 1976)
When gel filtration is used to transfer platelets from plasma into an established environment, alterations in platelet characteristics may result from the change in environment or from the effects of platelet contact with the gel matrix. To approach the problem of evaluating the relative contributions from these sources, a Sepharose 2B matrix was employed and platelets transferred from citrate anticoagulated PRP into autologous PPP to yield plasma-GFP. Platelet recoveries averaged 93 %. PRP: plasma-GFP pairs were found to be indistinguishable with respect to: morphology; ADP, thrombin or collagen-induced aggregation response; uptake of 5-hydroxytryptamine (5-HT) or adenosine; and thrombin or collagen-induced release of accumulated 5-HT or adenosine. Pairs are distinguishable by prostaglandin E2 synthesis assayed immediately after filtration.